PENGARUH SISTEM PEMBAYARAN CASH ON DELIVERY, ONLINE CUSTOMER REVIEW, DAN COSTUMER RATING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TOKOPEDIA DI YOGYAKARTA - Azzula Zamzam, Luh; Asteria, Beta (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
In conducting research, researchers utilized Tokopedia application users in Yogyakarta. This research aims to determine the influence of the cash on delivery payment system, online customer reviews, and customer ratings on the purchasing decisions of Tokopedia consumers in Yogyakarta. By utilizing the Tokopedia application, sampling in this study used purposive sampling techniques and utilized primary research data conducted by conducting surveys via Google Forms or questionnaires as the main data source with a Likerd scale of 1 to 4. The number of respondents in this study was one hundred and seventeen which were determined. with the Solvin formula. The methodology used in this research is multiple linear regression analysis using the SPSS version 18 application. The technique used in this research consists of multiple linear regression analysis tests, T tests, and coefficient of determination or R2 tests. The results of this research show that based on the results of the t test and f test the cash on delivery payment system, online customer reviews and customer ratings have a significant positive effect on purchasing decisions via the Tokopedia application in Yogyakarta.